STUDI POLA KOMUNIKASI PEMERINTAH DAN PESANTREN DALAM PENGEMBANGAN MASYARAKAT - Pramono, Muhammad Fajar (Universitas Sebelas Maret, 2016)
Historical development of boarding school itself can not be separated from the history of the development of Islam in the archipelago. Even genealogy boarding school education system can be traced from the time before the advent of Islam in Indonesia. Along with the development program in Indonesia, with the character of independence, Pondok Pesantren experiencing rapid development. Pondok Pesantren is not only incarnated as an educational institution of the people, but also as agents of change and community development. With the enactment of Law No. 20 of 2003 on National Education System, Boarding School entered a new phase in the world of education in this country, Pondok Pesantren has entered an integral part in the national education system. If all this has been donating all its schools for the benefit of citizens (state), then there must be a symbiotic mutualism between the two. It's time the state (government) pay serious attention to the continuity of boarding. If all this can exist with non-boarding schools, then the existence will be maximized if it is supported by the state. Moreover, the challenges ahead are certainly more severe because the social dynamics are also increasingly complex. Therefore, the necessary revitalization of the relationship between schools and the government during this flow. Pesantren has thus become and always become